Low-profile and wearable energy harvester based on plucked piezoelectric cantilevers - Pozzi, Michele; Almond, Heather; Leighton, Glenn J. T.; Moriarty, Roy J. (Society of Photo-Optical Instrumentation Engineers (SPIE), 2015)
The Pizzicato Energy Harvester (EH) introduced the technique of frequency up-conversion to piezoelectric EHs wearable on the lateral side of the knee-joint. The operation principle is to pluck the piezoelectric bimorphs with plectra so that they produce electrical energy during the ensuing mechanical vibrations. The device presented in this work is, in some ways, an evolution of the earlier Pizzicato: it is a significantly more compact and lighter device; the central hub holds 16 piezoelectric bimorphs shaped as trapezoids, which permits a sleek design and potentially increased energy output for the same bimorph area. Plectra were formed by Photochemical Machining of a 100-μm-thick steel sheet. To avoid the risk of short-circuiting, the plectra were electrically passivated by sputtering a 100 nm layer of ZrO2. Bench tests with the steel plectra showed a very large energy generation. Polyimide plectra were also manufactured with a cutting plotter from a 125μm-thick film. Besides bench tests, a volunteer wore the device while walking on flat ground or climbing stairs, with a measured energy output of approximately 0.8 mJ per step. Whereas most of the tests were performed by the traditional method of discharging the rectified output from the EH onto a resistive load, tests were performed also with a circuit offering a stabilised 3.3 V supply. The circuit produced a stable 0.1 mA supply during running gait with kapton plectra.